Information risk and underwriter switching in SEOs: Evidence from China - LUO, Wei (Institutional Knowledge at Singapore Management University, 2010)
In this paper we examine whether information risk affects underwriter switching in a seasoned equity offering (SEO) process. Building on previous research, we hypothesize that SEO firms and underwriters associate with one another by mutual choice, and firms with a low degree of information risk tend to match up with prestigious underwriters. Using a sample of SEO firms in China and employing accruals quality as a proxy of information risk, we find evidence consistent with our hypothesis: the information risk and the initial public offering (IPO) underwriters’ reputation at the time of the SEO jointly determine the probability that the firms will switch their underwriters. A mismatch between information risk and underwriter reputation increases the probability of an underwriter switching. Furthermore, if the firms decide to switch underwriters, then a lower degree of information risk is associated with a greater likelihood of changing to a more reputable underwriter. We also find that the relationship between information risk and the choice of underwriter reputation primarily exists in non-state-controlled companies.